Cost-effectiveness of the rural lifestyle eating and activity program (Rural LEAP) - Tiffany A. Radcliff; Murray J. Côté; Meena N. Shankar; Patricia E. Durning; Kathryn M. Ross; David M. Janicke; Christie A. Befort; Laurel S. Curran; Michael G. Perri (PLoS ONE, 2025)
Rural United States (U.S.) residents with obesity have unique challenges maintaining successful weight loss; tailored support resources such as individual behavioral coaching through telehealth are a cost-effective option. This study examined the cost-effectiveness of telephone-based individual coaching sessions for extended care after initial weight loss compared to an education-only control group. Trial data collected during a randomized trial conducted in rural counties in Florida from October 21, 2013, to December 21, 2018 informed the base case parameters. Using a program/participant perspective, cost-effectiveness was assessed for a 5-year time horizon using a discrete Markov model, with sensitivity analysis to test model assumptions. A 3% discount rate was used to value future time periods, and prices were inflated to 2024 values. Primary endpoints were the proportion of participants in each weight loss category, measured as a < 5%, 5–10%, or >10% reduction from baseline weight. Cost-effectiveness was assessed using program costs and participant-reported Quality-Adjusted Life Years (QALYs) and health care costs. Incremental cost effectiveness ratios (ICERs) were calculated for the end of the trial and 5 years post-trial. Cost-effectiveness used a willingness-to-pay threshold of $150,000/QALY. Results identified that intervention with 18 individual telephone counseling sessions was more expensive than the education/control program to deliver ($555/participant vs. $27/participant) but also more effective (34.2% with at least 10% weight loss vs. 17.0% for control at the end of the intervention), with 6.4% of modeled participants expected to maintain at least 10% in baseline reduction at year 5, compared to 5.4% for controls. Intervention participants were predicted to have modestly lower out-of-pocket prescription and other medical costs compared to participants in the control group, which offset some of the incrementally higher coaching program costs. Predicted ICERs at 5 years ranged from $7,731 to $8,156 per QALY gained through the individual coaching program. Findings contribute to evidence needed to identify cost-effective strategies for long-term weight management and disease prevention for at-risk populations.